THE RELATIONSHIP BETWEEN STRESS LEVELS AND SMOKING BEHAVIOR IN UIN NORTH SUMATERA MEDAN TUNTUNGAN STUDENTS - Rambe, Siska Rahmadani; Sa’adah, Naila; Hidayah, Nurul; Amanda, Dea; Wahyudi, Wahyudi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Smoking is one of the most serious public health problems in Indonesia, which affects people of all ages, especially among university students. Various psychological factors are often associated with college students smoking habits, one of which is stress. Stress can come from various sources, such as academic pressure, financial problems, or worries about the future. This study aims to analyze the relationship between stress levels and smoking behavior in UIN North Sumatra Medan Tuntungan students. This type of research uses a quantitative approach with a case control design, with sampling techniques using accidental sampling involving 80 respondents consisting of 40 student smokers and 40 student non-smokers. Data were collected using a standardized questionnaire that had been tested for validity and reliability to measure stress levels and smoking behavior. Bivariate data analysis was conducted using chi square test. The results showed that 23 respondents (57%) from the case group were 21 to 24 years old, and 25 respondents (62.5%) from the control group were 17-20 years old. It was found that most respondents were at a moderate level of stress in the case group and control group. Where as many as 30 respondents (75%) in the case group, and 32 respondents (80%) in the control group. The conclusion of this study is that statistically there is no significant relationship between stress levels and smoking behavior in UIN North Sumatra Medan Tuntungan students, with the results of the chi square test showing a p value of 1.0 (p>0.05).